Balancing Leadership and Workload: Examining Their Impact on Employee Job Satisfaction in the Security Services Industry - Putri, Sasha Triana; Suwarto, Suwarto; Titing, Andry Stepahnie (Pascasarjana STIE Amkop Makassar, 2025)
This study examines the influence of leadership style and workload on employee job satisfaction, focusing on security personnel at PT. Kartika Cipta Indonesia. Using a quantitative approach and Structural Equation Modeling-Partial Least Squares (SEM-PLS), this research analyzes the relationships between leadership style, workload, and job satisfaction. Data were collected through a structured questionnaire distributed to 155 respondents, with measurement reliability assessed through Composite Reliability and Cronbach’s Alpha. The findings indicate that leadership style has a positive and significant impact on job satisfaction (β = 0.459, T = 5.382, P = 0.000), suggesting that effective leadership characterized by support, collaboration, and clear communication enhances employee satisfaction. Conversely, workload negatively affects job satisfaction (β = -0.464, T = 4.723, P = 0.000), implying that excessive job demands contribute to stress, burnout, and reduced work engagement. These results align with previous studies, reinforcing the importance of leadership effectiveness and workload management in organizational settings. The study highlights the need for organizations to foster supportive leadership while implementing strategic workload distribution to maintain a productive and satisfied workforce. Future research should explore the mediating effects of work engagement, psychological resilience, and organizational culture to deepen the understanding of these relationships across different industries. Keywords: Leadership style, workload, job satisfaction, SEM-PLS, security personnel, employee well-being